Learning Needs Software Development in Determining Community Learning Needs Priority at the Community Learning Center (CLC) - Purnomo, Purnomo; Nudiati, Deti; Lutfiansyah, Dadang Yunus; Putra, Apriza Hongko; Sulistiono, Eko (Journal of Nonformal Education, 2024)
Challenges to Industry 4.0 are faced by the field of community empowerment, which is implemented by community education programs. To face this challenge, the position of technology in community empowerment programs is a strategic approach to achieving community needs. One of the CLCs in Pagerwangi Village, Lembang District, experienced problems in collecting data on community learning needs, so a technological breakthrough was needed to facilitate facilitators in collecting data along with mapping the needs of community empowerment programs so that they could be achieved. Through the Digital Needs Assessment, facilitators will find it easier to explore, record, process, analyze, and report data. The purpose of this research is to develop a prototype of the Digital Needs Assessment software that is effectively developed for community use in determining the priority of community education and learning needs. This research method uses a quantitative approach in the form of descriptive statistics with a total of 42 respondents who are CLC facilitators, carried out for 5 months, from February 2023 to June 2023. Based on the research results, the Digital Needs Assessment software can improve the competence of CLC facilitators, especially in processing data or information on the results of identifying community learning needs